A Exploring Technology and Livelihood Education in Lower Elementary Grades: Instructional Practices and Skill Development: Exploring Technology and Livelihood Education in Lower Elementary Grades: Instructional Practices and Skill Development - Cabacungan, Moniza; Martin, Matronillo (Studies in Technology and Education, 2026)
Technology and Livelihood Education (TLE) is traditionally introduced in the upper elementary or junior high school levels, where learners are expected to engage with more specialized technical and vocational competencies. However, foundational exposure to TLE-related skills during the lower elementary years may play a critical role in developing learners’ practical abilities, work habits, creativity, and problem-solving skills. This study examines the instructional practices used in introducing Technology and Livelihood Education concepts in Grade 3 and analyzes their influence on learners’ skill development. Using a descriptive–correlational design with an embedded qualitative component, the study documents classroom-based instructional strategies and assesses learners’ emerging skills in basic tool use, simple processes, cooperation, and task completion. Classroom observations and teacher interviews were conducted to capture both instructional patterns and contextual challenges. Findings suggest that age-appropriate, activity-based, and contextualized instructional practices support the development of foundational TLE skills among Grade 3 learners. The study highlights the pedagogical value of introducing TLE concepts early and provides implications for curriculum design, teacher preparation, and instructional planning in lower elementary education.